The efficacy of curcumin/Qing Dai combination in children with active ulcerative colitis: a multicenter retrospective cohort study - Nachum, Nurit Loberman; Salomon, Nir; Yerushalmy-Feler, Anat; Weintraub, Yael; Yogev, Dotan; Granot, Maya; Haberman, Yael; Ben-Horin, Shomron; Weiss, Batia (Frontiers in Pediatrics, 2024)
Background Curcumin and Qing Dai (QD) are herbal extracts that recently showed efficacy in treating inflammatory bowel disease (IBD). Since 2016, a combination of curcumin with QD (CurQD) has been employed in our center for management of active ulcerative colitis (UC). Objectives We report the effectiveness and safety of CurQD therapy in children with mild-moderate UC or IBD-unclassified (IBD-U). Design A multicenter retrospective study. Methods Children aged ≤OP18 years who were treated with CurQD during 2017–2021 were included. Disease activity measures were Pediatric UC Activity Index (PUCAI), and fecal calprotectin (FC). The primary outcome was a decrease in PUCAI by ≥10 points, FC normalization (≤100 µg/gr when baseline ≥300 µg/gr) or a ≥ 50% decrease in FC. Results Of 30 patients (60% males, mean age 14 ± 3.9 years), 15 (50%), 13 (43%), and 2 (7%) had pancolitis, left-sided colitis and proctitis, respectively. The daily medication dose was 0.5–3 gm QD with 1–4 gm curcumin. Concomitant treatment at induction was corticosteroids (19%), biologics (28%) and 5-aminosalicylic acid (40%). The mean duration of induction was 11.6 weeks [95% confidence interval (CI) 10.2–13.1, range 8–16]. PUCAI decreased from a mean of 31.3 (95% CI 26.6–36.0, range 5–60) to 10.9 (95% CI 7.6–14.4, range 5–35) (n = 26, p < 0.001). FC response and normalization occurred in 11/12 and 7/12 patients, respectively. The median decline in FC was from 749 µg/gm [interquartile range (IQR) 566–1000] to 39 µg/gm (IQR 12–132) (n = 15, p = 0.04). During follow-up (median 8 months, IQR 6–10), 10 patients (33%) flared; five of them regained remission or responded to a treatment change. Of 18 patients treated beyond induction, 12 (67%) achieved clinical response and 10 achieved clinical remission by the end of follow up. Conclusion CurQD may be effective and safe as an add-on option to conventional management, for induction and maintenance in children with mild-moderate UC/IBD-U.